Incidence, features and management of radionecrosis in melanoma patients treated with cerebral radiotherapy and anti‐PD‐1 antibodies. (3rd March 2019) - Pires da Silva, Ines; Glitza, Isabella C.; Haydu, Lauren E.; Johnpulle, Romany; Banks, Patricia D.; Grass, George D.; Goldinger, Simone M. A.; Smith, Jessica L.; Everett, Ashlyn S.; Koelblinger, Peter; Roberts‐Thomson, Rachel; Millward, Michael; et al.
Abstract: Background: Brain radiotherapy is used in the management of melanoma brain metastases (MBM) and can result in radionecrosis. Anti‐PD‐1 is active in the brain and may increase the risk of radionecrosis when combined with radiotherapy. We studied the incidence, associated factors and management of radionecrosis in longer‐term survivors with MBM treated with this combination. Methods: Patients with MBM treated with radiotherapy and anti‐PD‐1 who survived >1 year were identified to determine radionecrosis incidence (Cohort A, n  = 135). Cohort A plus additional radionecrosis cases were examined for factors associated with radionecrosis and management (Cohort B, n  = 148). Results: From Cohort A, 17% developed radionecrosis, with a cumulative incidence at 2 years of 18%. Using Cohort B, multivariable analysis confirmed an association between radionecrosis and elevated lactate dehydrogenase ( p  = 0.0496) and prior treatment with ipilimumab ( p  = 0.0319). Radionecrosis was diagnosed based on MRI (100%), symptoms (69%) and pathology (56%). Treatment included corticosteroids, bevacizumab and neurosurgery. Conclusions: Radionecrosis is a significant toxicity in longer‐term melanoma survivors with MBM treated with anti‐PD‐1 and radiotherapy. Identification of those at risk of radionecrosis who may avoid radiotherapy is required.